Multiple myeloma: imaging evaluation of skeletal disease - Carlton Sexton; Candice Crichlow (Greater Baltimore Medical Center, 2013)
This patient is a 56-year-old woman with a history of IGG κ multiple myeloma diagnosed 15 years prior to admission. She had widespread lytic bone lesions and pathological fractures, which remarkably had not been accompanied by significant pain, but were mostly refactory to chemotherapy